Minimizing the Effect of Frost in sugarcane crop - Singh, Jugraj; Kaur, Jagroop (Indian Farming, 2017)
Farmers can protect their sugarcane crop from frost and enhance the cane yield by adopting good farm practices as recommended by the scientists.